Efficacy of prophylactic use of tranexamic acid in reduction of blood loss in benign hysterectomy: a randomised controlled trial - Nandi, Manisha; John, Lopamudra B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Aim of current study was to determine the efficacy of tranexamic acid in the reduction of blood loss during hysterectomy for benign indications. Methods: This is a randomized controlled trial in a tertiary care teaching hospital in Pondicherry. The study population was 108. Participants were allocated into 2 groups: Group A (N=54) and group B (N=54) based on computer generated random numbers. Group A (N=54) comprised of participants undergoing hysterectomy with prophylactic intravenous tranexamic acid (1 gram in 100 ml of 0.9% normal saline) which was further subdivided into A1 (N=27) and A2 (N=27) undergoing abdominal and vaginal hysterectomy respectively. Group B: comprised of participants undergoing hysterectomy without tranexamic acid, further subdivided into B1 (N=27) and B2 (N=27) undergoing abdominal and vaginal hysterectomy respectively. The mean blood loss during the intraoperative and post-operative periods was calculated and compared between the groups. Results: Participants in Group A who received prophylactic tranexamic acid were found to have less blood loss compared to the control population in Group B. The difference between the means was statistically significant. Conclusions: We concluded that tranexamic acid should be considered as prophylactic treatment for hysterectomy to reduce the risk of substantial blood loss and the need for blood transfusion and early recovery.